An analysis of the two-tier foreign exchange market - BARATTIERI, V.; RAGAZZI, G. (PSL Quarterly Review, 2014)
This paper analyses the possible effects of the two-tier foreign exchange market. This system, which has been in operation in Belgium for over 15 years, has recently found new supporters, as is indicated by the fact that during the international monetary crisis of May 1971 the EEC Commission counselled its adoption. The author first analyses the reasons which may justify restrictions on the freedom of capital movements, both in the short run and in the longer term. Some of the technical characteristics of a two-tier foreign exchange market are then examined before the well-known Mundell analysis of the efficiency of monetary and fiscal policy in an open economy is extended to the case of a country with such a system. Finally, the author draws some conclusions and compares a two-tier system with other instruments designed to reduce the undesired repercussions of high capital mobility. JEL: F31, F36, E62